5.2 COGNITIVE BEHAVIORAL THERAPY FOR SOCIAL ACTIVATION IN RECENT-ONSET PSYCHOSIS: RANDOMIZED CONTROLLED TRIAL. (9th April 2019) - Velthorst, Eva; Pos, Karin; Franke, Nathalie; Smit, Filip; Wijnen, Ben; Van der Gaag, Mark; Meijer, Carin; Haan, Lieuwe De; Schirmbeck, Frederike
Abstract: Background: Negative symptoms largely account for poor outcome in psychotic disorders but remain difficult to treat. A cognitive– behavioral approach to these symptoms showed promise in chronic schizophrenia patients. We explored whether a combination of group and individual treatment focused on social activation (CBTsa) could benefit patients recently diagnosed with a psychotic disorder. Methods: A single-blind randomized controlled trial enrolled 99 participants recently diagnosed with schizophrenia or a related disorder that received treatment as usual (TAU; n 50), or TAU plus CBTsa (n 49). Negative symptoms (Brief Negative Symptom Scale) and social withdrawal (Positive and Negative Syndrome Scale) were primary outcomes. Secondary outcome measures included dysfunctional beliefs (Dysfunctional Attitudes Scale-Defeatist Performance Attitude), stigma (ISMIS), and symptom severity and functioning as measured with the Global Assessment of Functioning (GAF). Outcomes were compared directly posttreatment and at follow-up (6 months posttreatment). Results: Intention-to-treat analyses showed significant improvement in GAF symptoms (p .02, d 0.36) and a decrease in negative symptoms on trend level (p .08, d 0.29) in CBTsa compared to TAU at posttreatment. These group differences were no longer apparent at 6 months follow-up. Social withdrawal and negative symptoms improved over time in both conditions. Conclusions: The current trial showed small positive effects on symptom severity posttreatment but did not demonstrate maintenance of longer-term effects in favor of the CBTsa group. Findings suggest that the treatment duration may have been too short to change dysfunctional beliefs, a potentially important maintaining factor of negative symptom severity. Longer intervention periods in later, more stable stages of the illness when intensive standard treatment has tapered off may yield more beneficial effects.